Evaluate the Correlation between the TIMI Frame Count, IMR, and CFR in Coronary Microvascular Disease - Xinye Xu; Jinbao Zhou; Yongzhen Zhang; Qian Li; Lijun Guo; Yanyang Mao; Liyun He (Journal of Interventional Cardiology, 2022)
Objective. To evaluate the correlation between the TIMI frame count, IMR, and CFR in coronary microvascular disease (slow flow phenomenon). Methods. TFC and IMR were recorded in the nitroglycerin and ATP administration states, and the relationship between TFC, IMR, and CFR in specific states was analyzed. Results. A total of 41 patients with baseline TFC >25 frames on coronary angiography were enrolled, and nitroglycerin reduced TFC by 50% from baseline in 24 (58.54%) patients; 16 of the remaining 17 patients were able to achieve a 50% reduction in TFC by further intracoronary ATP injection. 10 patients were further tested for IMR, and the results showed significant correlations between baseline TFC and IMR (r = 0.775, P=0.008), TFC and IMR after nitroglycerin (r = 0.875, P=0.001), and the minimal TFC and IMR that could be obtained with nitroglycerin or ATP administration (r = 0.890, P=0.001). There was also a significant correlation between the proportional improvement in TFC and CFR before and after nitroglycerin injection (r = 0.685, P=0.029). In addition, we observed a lower IMR measured after nitroglycerin than after ATP in three patients, suggesting that CMD may be dominated by NO-sensitive vascular such as prearterioles and that an extensive analysis of the target site of CMD may be achieved by stepwise drug administration. Conclusion. Induction of TFC in different states by a stepwise drug approach may serve as a potential primary screening method for coronary microcirculatory dysfunction, thereby reducing the need for further IMR or CFR testing.